2023
DOI: 10.3389/fnut.2022.993061
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the malnutrition on mortality in Rheumatoid arthritis patients: A cohort study from NHANES 1999–2014

Abstract: BackgroundPatients with Rheumatoid arthritis (RA) are prone to malnutrition. However, it is rare studies assessing the relationship between malnutrition and all-cause mortality in patients with RA.ObjectiveTo investigate the relationship between malnutrition and all-cause mortality in patients with RA in a large national sample cohort.MethodsWe analyzed data on 1,976 adults ≥ 18 years of age during National Health and Nutrition Examination Survey (NHANES) 1999–2014. We chose the Controlled Nutritional Status S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Our study investigated HALP's role in both classifications, finding lower median HALP scores in participants with rheumatoid arthritis. This aligns with prior research indicating that the controlled nutritional status score (CONUT) and the nutritional risk index (NRI), which include nutritional markers such as albumin, body weight, and lymphocyte count, are associated with increased all-cause mortality in rheumatoid arthritis (35).…”
Section: Arthritissupporting
confidence: 86%
“…Our study investigated HALP's role in both classifications, finding lower median HALP scores in participants with rheumatoid arthritis. This aligns with prior research indicating that the controlled nutritional status score (CONUT) and the nutritional risk index (NRI), which include nutritional markers such as albumin, body weight, and lymphocyte count, are associated with increased all-cause mortality in rheumatoid arthritis (35).…”
Section: Arthritissupporting
confidence: 86%
“…Khatami ( 35 ) emphasized the critical role of malnutrition in the development of systemic inflammation and associated pathology. Additionally, a cohort study reported a heightened risk of all-cause mortality in RA patients who were malnourished ( 12 ). Therefore, we contended that assessing the prognosis of RA patients should consider both inflammation and malnutrition concurrently.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive protein catabolism evoked by inflammatory cytokines and disuse atrophy due to functional impairment contributes to this progression ( 34 ). Malnutrition further increases the risk of death in RA patients ( 12 ). Thirdly, increased BMI is strongly associated with poor prognosis in patients with RA ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several new laboratory-based nutritional indicators have emerged in recent years, including the Controlling Nutritional Status (CONUT) Score ( 8 ), Advanced Lung Cancer Inflammation Index (ALI) ( 9 ), Geriatric Nutritional Risk Index (GNRI) ( 10 ), Prognostic Nutritional Index (PNI) ( 11 ), Triglycerides (TG) × Total Cholesterol (TC) × Body Weight (BW) Index (TCBI) ( 12 ), and Albumin-to-Globulin Ratio (AGR) ( 13 ). CONUT has been used as an indicator for assessing the risk of mortality in patients with rheumatoid arthritis and type 2 diabetes ( 14 , 15 ). ALI has been used to predict the prognosis of hypertension and heart failure ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%